2002
DOI: 10.1002/1521-3951(200201)229:1<553::aid-pssb553>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structures of a Quantum Well of A1-xBx Alloy Semiconductor in the Coherent Potential Approximation

Abstract: We have theoretically studied the electronic and optical properties of a quantum well (QW) in which the well region is constructed from a binary alloy semiconductor A 1--x B x in the coherent potential approximation (CPA). A tight binding model is used for a single particle (electron, hole, Frenkel exciton) in the well composed by a rectangular array of N x  N y  N z sites. The effect of the diagonal randomness is reduced to the coherent potential S(E), which is assumed to be the same for all sites, and is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…( 10) is obtained, as it was assumed in Refs. [5,6]. In the present work, the behavior of this function in each layer of the system which depends on the number of layers, alloy concentration and the strength of scattering processes via the self-energy will be studied in Sec.…”
Section: Model and Formalismmentioning
confidence: 99%
See 3 more Smart Citations
“…( 10) is obtained, as it was assumed in Refs. [5,6]. In the present work, the behavior of this function in each layer of the system which depends on the number of layers, alloy concentration and the strength of scattering processes via the self-energy will be studied in Sec.…”
Section: Model and Formalismmentioning
confidence: 99%
“…It has been demonstrated that, by using semiconductor nanostructures instead of bulk structures, the threshold current may be reduced by more than ten times due to the abrupt energy dependence of the density of states in low-dimensional structures which can enhance the light amplification mechanisms and thus allows lasing to occur at lower currents [3]. Furthermore, the optical absorption in semiconductors which is governed by the electronic density of states, is strongly affected by the impurities [4][5][6]. For instance, using a semiconducting alloy A 1−x B x , composed of two semiconductors A and B with different band gap energies, one can tune the operation of an optical device at desired wavelength.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies [21][22][23], by applying the single-site coherent potential approximation (CPA) [24] to semiconductor alloy multilayers, the effects of chemical (nonmagnetic) disorder on optical absorption spectrum were investigated. The results showed that, the photon absorption by the system is layer dependent and strongly changes by variation of the scattering-strength of the chemical impurities [21].…”
Section: Introductionmentioning
confidence: 99%